Perbedaan Coping Stres terhadap Stres Akademik antara Siswa Laki-laki dan Perempuan pada Ujian Matematika - Dianti, Nabilah Dwi; Handayani, Isnaini (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2025)
Academic stress in students can negatively impact math exam results. Everyone, especially students, has different stress management strategies. This study aims to identify the differences in stress coping strategies high school students use on mathematics exams. This study uses a quantitative research method with a descriptive analytical approach. The analysis technique includes percentage and trend analysis from a questionnaire with 56 statements about high school students' stress-coping strategies in mathematics exams. This study population consists of 94 students, with a sample of 37 male and 57 female students. This study uses purposive sampling. This study found that 83.78% of the 37 male students and 64.91% of the 57 female students in grade X used problem-focused coping strategies in mathematics exams, unaffected by gender differences. Future research is recommended to improve understanding of the factors that influence stress coping strategies, measure the relationship between supportive factors and the stress coping strategies used, and determine the relationship between stress coping strategies and students' mathematics exam results.